OpenMP in the petascale era 7th International Workshop on OpenMP, IWOMP 2011, Chicago, IL, USA, June 13-15, 2011. Proceedings - IWOMP Conference 2011 Chicago, Ill.); Chapman, Barbara 1954-.; SpringerLink (Online service). (Berlin Springer, 2011)
This book constitutes the refereed proceedings of the 7th International Workshop on OpenMP, IWOMP 2011, held in Chicago, IL, USA in June 2011. The 13 revised full papers presented were carefully reviewed and selected for inclusion in the proceedings. The papers are organized in topical sections on using OpenMP with application, tools for OpenMP, extensions of OpenMP, and implementation and performance.
Electronic reproduction.
Keywords: OpenMP -- Congresses; Parallel programming (Computer science) -- Congresses; Parallel processing (Electronic computers) -- Congresses; Electronic books